Chemical characterization of the lipid fractions of pumpkin seeds. Issue 1 (9th February 2015) - Veronezi, Carolina Médici; Jorge, Neuza
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to characterize the pumpkin (Cucurbita sp) seed oil from the varieties Nova Caravela, Mini Paulista, Menina Brasileira (Cucurbita moschata) and Moranga de Mesa (Cucurbita maxima) as to their physicochemical properties, vitamins and fatty acid and triacylglycerols profiles. Design/methodology/approach – The oils were extracted from oilseeds by the Bligh and Dyer (1959) method, and chemical characterization was performed by using standard methods for oils and fats. The vitamin A and E content, fatty acid profile and triacylglycerols profile also were determined. Findings – About the chemical properties, the oils showed values within the range for edible vegetable oils. The oil from variety Nova Caravela stood out for presenting better quality, as it showed lower values of free fatty acids, acidity and peroxides. However, it was found that the Moranga de Mesa oil was the most unsaturated, due to the high refractive and iodine index, and was also reported to have lower oxidative stability. Among the unsaturated fatty acids, ranging from 70 to 78 per cent of the total obtained, linoleic and oleic acids stood out, while among the saturated ones, palmitic and stearic did. Practical implications – These seeds are rich in high-quality lipids; therefore, their use could help to reduce the amount of waste produced in the industries, and consequently reduce environmental contamination. This study showed that the seeds could be used as a raw material for oil extraction, and also could be used for developing functional foods instead of being discarded. Originality/value – This study provides valuable information about the quality and fatty acid contents of pumpkin seed oils consumed in Brazil.